Assessment of energy demand-based greenhouse gas mitigation options for Canada's oil sands. (20th December 2019) - Katta, Anil Kumar; Davis, Matthew; Subramanyam, Veena; Dar, Anum Fahim; Mondal, Md Alam Hossain; Ahiduzzaman, Md; Kumar, Amit
Abstract: The main objective of this study is to assess energy-use reduction strategies in extraction and upgrading of oil sands for greenhouse gas mitigation in Canada's oil sands sector. A bottom-up integrated resource-planning model for oil sands extraction and upgrading processes was developed. The model is a novel application of an energy accounting-based framework and accurately simulates energy demand and supply in the oil sands from 2007 to 2050. Thirty energy-use reduction scenarios were evaluated covering in situ extraction, surface mining, and bitumen upgrading processes. The energy savings, greenhouse gas emission mitigation, and costs associated with each scenario were determined with the model. Implementing in situ energy-use reduction measures resulted in the highest single measure greenhouse gas mitigation potential of 86 million tonnes CO2 e at a marginal greenhouse gas abatement cost of -$91/tonne of CO2 e by 2050. For the scenarios in surface mining and bitumen upgrading, the highest single measure greenhouse gas mitigation potentials are 17 and 16 million tonnes CO2 e by 2050 at marginal greenhouse gas abatement costs of -$65/tonne of CO2 e and -$21/tonne of CO2 e, respectively. All strategies result in a negative $/tonne of CO2 e cost, indicating a net benefit for investing in the strategies. If the strategies are implemented together, there is an ultimate potential to reduce sector-wide cumulative energy consumption and greenhouse gas emissions in the oil sands by 8% and 7%, respectively, by 2050. Decision-makers at company or government levels can use these results to support both environmental and cost-saving initiatives. Graphical abstract: Image 1 Highlights: A bottom-up energy supply-demand model for the oil sands sector was developed. Sector-wide energy consumption could be reduced up to 8%. An annual average of 7.6 million tonnes of GHG emissions could be mitigated. 65% of evaluated GHG mitigation potential is from in situ extraction. All GHG emission mitigation strategies have negative marginal abatement costs.